A large-scale synthesis of photoluminescent carbon quantum dots: a self-exothermic reaction driving the formation of the nanocrystalline core at room temperature. Issue 19 (14th September 2016) - Chen, Bin Bin; Liu, Ze Xi; Deng, Wen Chan; Zhan, Lei; Liu, Meng Li; Huang, Cheng Zhi
Abstract : Core–shell structural carbon quantum dots (CQDs) are prepared through a highly efficient self-exothermic reaction at room temperature, which possess 24.6% absolute quantum yield and can be well applied for analysis applications. Abstract : Carbon quantum dots (CQDs), a rising star family in photoluminescent (PL) nanomaterials, have been identified to have a core–shell structure with the nanocrystalline core of sp 2 -hybridized carbon clusters and the functional group formed shell of sp 3 -hybridized carbons, in which the core formation usually needs high-temperature carbonization. Herein, we develop a route to prepare CQDs on a large scale by using hydroquinone and ethylenediamine (EDA) as the precursors and the EDA-catalyzed decomposition of hydrogen peroxide at room temperature. The released heat from this highly exothermic reaction system can rapidly prompt the formation of the nanocrystalline core. The as-prepared CQDs in situ show green PL properties around 525 nm under excitation at 320 to 420 nm with the absolute quantum yield of 24.6%, and can find applications in visual analysis and other fields.